PENGEMBANGAN MODUL STRUKTUR ATOM TERINTREGRASI AUGMENTED REALITY - Widiani, Astry Risqi; Prasetya, Agung Tri; Kurniawan, Cepi (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
Education in Indonesia is increasingly oriented toward 21st-century learning, which requires students to develop skills that enable them to face global challenges and compete in a rapidly changing world. This study aimed to develop and evaluate the feasibility of an augmented reality (AR)-integrated atomic structure module as an alternative learning resource in chemistry education. The research adopted a development design based on the 4D model—define, design, develop, and disseminate. Product feasibility was evaluated through expert validation involving material and media specialists, as well as assessments by chemistry teachers and students. The findings revealed that the AR-based atomic structure module is highly feasible and pedagogically appropriate as a learning resource. Validation results indicated average scores of 98% from material experts and 96% from media experts. Readability tests with students yielded a score of 93% (very good), while teachers rated the module’s practicality at 97% (very feasible). These results suggest that the developed module not only provides accurate content and engaging visualizations but also enhances students’ comprehension, motivation, and independent learning. Therefore, the AR-based module can serve as an innovative and effective tool for chemistry learning, particularly in understanding abstract concepts such as atomic models, electron configurations, and orbitals. Furthermore, this study contributes to the growing body of research on AR applications in science education by demonstrating its potential to improve learning outcomes and foster 21st-century skills.